Chemostratigraphy (TOC, 13C, 18O) around the Pliensbachian/Toarcian boundary in the reference section of Peniche (Lusitanian Basin, Portugal) - Veiga de Oliveira, L. C. (2007)
This work presents the chemostratigraphy analysis based on total organic carbon (TOC) and the evolution of the carbon and oxygen stable isotopes in the whole rock samples around the Pliensbachian/Toarcian boundary in the Peniche section (uppermost part of Lemede Formation and lowermost part of Cabo Carvoeiro Formation). These are partial results which form part of a group of studies, being processed, that include isotope analyses of 87Sr/86Sr, 18O, 13C and major, minor and trace elements in whole rock and belemnites.